Rancang Bangun Sistem Monitoring Tanaman Cabe Jamu Terhadap Mekanisme Lingkungan Tumbuh pada Web - Aulian Vardani; Farida Arinie (Politeknik Negeri Malang, 2019)
Jamu chili or Javanese chili (Piper retrofractum Vahl.) Is a medicinal plant that has been used since ancient times as an ingredient in cooking, drinks and traditional medicine, such as to treat low blood pressure, colds, impotence as well as to clean the uterus after childbirth. . Besides herbal chilies as medicinal plants, the price of herbal chilies is expensive and their production is utilized domestically and exported to, among others, Singapore, Hong Kong, Malaysia and India. Herbal chilli plantations are spread across all districts, especially in Madura Island, namely in Sumenep District 1,709 ha, Sampang 1,017 ha, Pamekasan 715 ha and Bangkalan 356 ha. In Lamongan Regency, there is an area of ??276 ha. The area of ??herbal chilies in Lampung Province is 630 ha. However, despite the many benefits and have been exported abroad, the herbal chili plants have not been well controlled by the farmers, which causes the herbal chili plants to die before they bear fruit. In this research, a web-based monitoring system design will be made based on the level of soil acidity and soil moisture. The sensor for soil acidity uses a pH meter and for soil moisture uses a soil moisture sensor. Data will be stored in the database and displayed on the web. Soil acidity and soil moisture data will be sent via the internet to the database.